A METHODOLOGY PROPOSAL FOR CONDUCTING MACRO-PK TEST ON LIGHT SPINNING OBJECTS, IN A NON-CONFINED ENVIRONMENT - Dullin, Eric; Jamet, David (Journal of Scientific Exploration, 2018)
For more than a century, there has been much debate around the use of telekinesis-psychokinesis (TK[1]) to explain the rotating movement of light objects on an upright standing needle in the proximity of a hand. Thermally-induced aerodynamic effects have been considered as likely physical explanation factors. Despite this controversy, many still upload videos claiming the phenomenon on the internet. Most of the scientific studies performed were focused on whether or not the effects could be observed if some physical constraints were added, in order to avoid the aerodynamics factor, or if the same results could be reproduced using some thermic or/and aerodynamic artefacts instead of a human presence. The first approach runs the risk of inhibiting a phenomenon about which little is known. The second has not yet shown clear reproducible experiences, which produce the same results as with a human presence, except in very specific situations. Our objective is to be able to detect and study psychokinesis in confined and non-confined environments with scientific measurement tools. Our hypothesis is that there could be a way to separate psychokinetic effects from aerodynamic effects, even in a non-confined environment, so avoiding the drawbacks of the first approach. This technique of approaching anomalous perturbations could be described as partial physical isolation of the target system, with a measurement system ensuring control of the remaining known effects. It can be related to two other techniques previously described (May, Uttis & Spottiswoode 1995: Introduction). From the beginning, the LAPDC has been fostering a PKers (subjects practicing psychokinesis) volunteer team in order to do the experiments. From 2012 to 2016, we have been developing specific scientific methods in order to study the psychokinesis effect on a spinning mobile with or without confinement. More specifically, we developed a protocol starting with particle image velocimetry (PIV) in order to measure the air-flow speeds around the mobile. Further research has driven us to create a set of processes using MATLAB, which we named Scan-Flow-Mobile. It has enabled us to construct one global model, integrating air flow movements and mobile movements, and scrutinize it. Using this, we were able to compare different experiments. We conducted a thorough analysis of the interaction between the mobile and the air flows, and studied the cause-and-effect relationships between their movements. A review of the “spinning mobiles” literature of the last century, either with psychokinetic hypothesis and aerodynamic/thermic explanation, has been done. We also studied other potential causes of motion such as electrostatic forces, magnetism, vibrations, and the impact of radiation. Then, as a pilot study, we conducted eight experiments in non-confined environments, with three set-up categories: one where the mobile motion was driven by generated air flows (A), one in which a motor drove the mobile (M) and the last one where a PKer drove the mobile (PK). The ratio (mobile speed/mobile periphery airflow speed) was used as a way to compare experiences between experiments and categories. In this paper we focus only on the methodological approach and so on the categories A and M. With regard to this ratio, the category M experiments stayed above or equal to two, while category A was below or equal to 0.5. This separated clearly pure aerodynamic effects (A) from the motor driven effect (M). So the methodology could be a good candidate to conduct macro-PK test in a non-confined environment with the capability to eliminate or not the aerodynamic effect as explanation. A potential bias and errors analysis is presented, which takes into account the difference between air-flow and smoke-particle velocity, the mean speed evaluation for the air flows and the mobile. Indeed, we evaluated the potential error on the ratio air-flow speed/mobile speed as approximately +/- 8.9%, which is marginal compared to the ratios differences between categories A and M. The methodology presents also some features that helps detect tricks that could be tried by some misbehavioring PKer (as mouth air blowing, hand move...). We’ll look to improve the total measurement process documentation, in order to give other laboratories the possibility to test it in their experiments. [1] TK: at the LAPDC we use TK for telekinesis. For this paper we will use PK for psychokinesis. This point is discussed at the end of the introduction.